INNOVATIVE TOURISM PRODUCTS AS SUSTAINABLE SOLUTIONS FOR EMERGING ECONOMIES - Rozalia Gabor, Manuela; Dana Oltean, Flavia; Coca, Andrei (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2023)
The current trend in tourism is no longer one of relaxation in the two important seasons but of experiential tourism, developing of new types of tourism, each country identifying (but especially reinventing) its own potential and promoting it below the form of innovative tourist packages and/or products and/or services. Innovation as a concept is setting up the scene for economic growth and is an important tool for economic progress and competitiveness. The aim of this research is to make a bibliometric analysis to find out the most important aspects of innovation linked to tourism as sustainable solutions for tourism in emerging economies. As methods for bibliometric analysis the VOSviewer 1.6.18 software was used on the Web of Science papers to find out the research concepts linked to innovation and tourism. Also, we applied Google Trends search for some of the newest types of tourism to find out the interest of tourists over the last two decades (2010 – 2023) for innovative products from tourism industry (such as: babymoon, adventure, medical, dental, hunting, ecotourism, heritage, museum, etc.). The results emphasis the relation between innovation, tourism, information technology (internet, smart tourism, innovative technology), stakeholders (governments, organizations, municipalities, communities), tourism experience, tourism destination, tourism services, product innovation, competitiveness advantages, economic development, performance, cultural heritage, rural area, ecotourism.